2006
DOI: 10.1007/s11420-006-9031-2
|View full text |Cite
|
Sign up to set email alerts
|

MRI Evaluation of Isolated Arthroscopic Partial Meniscectomy Patients at a Minimum Five-Year Follow-up

Abstract: Despite optimal preoperative prognostic factors and excellent functional outcomes, MRI evidence of early articular cartilage degeneration was present in both partial medial and lateral meniscectomy patients at a minimum 5-year follow-up. Results support the use of cartilage-sensitive MRI as a noninvasive screening technique to evaluate cartilage changes after arthroscopic partial meniscectomy and may help to counsel the high-risk patient in regard to postoperative activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
4
22
0
1
Order By: Relevance
“…The use of radiography to assess the disease status of the knee has limited the capacity of these studies to identify the early effect of meniscectomy on articular cartilage and subchondral bone. Previous MRI studies have shown increased cartilage loss and cartilage defects and subchondral sclerosis in the tibiofemoral joint 2-8 years post-meniscectomy [9,42,29]. Consistent with these studies, this study showed APMM was associated with an increased risk of tibiofemoral cartilage defects, independent of tibial cartilage volume and bone area.…”
Section: Discussionsupporting
confidence: 89%
“…The use of radiography to assess the disease status of the knee has limited the capacity of these studies to identify the early effect of meniscectomy on articular cartilage and subchondral bone. Previous MRI studies have shown increased cartilage loss and cartilage defects and subchondral sclerosis in the tibiofemoral joint 2-8 years post-meniscectomy [9,42,29]. Consistent with these studies, this study showed APMM was associated with an increased risk of tibiofemoral cartilage defects, independent of tibial cartilage volume and bone area.…”
Section: Discussionsupporting
confidence: 89%
“…Similar disease processes could occur in humans, particularly in post-traumatic osteoarthritis 44 45. Indeed, despite the absence of clinical symptoms, early articular cartilage degeneration does occur in the operative compartment a minimum of 5 years after partial meniscectomy, and subchondral bone changes may occur after cartilage involvement 44 45…”
Section: Cartilage Damage/normal Bmdmentioning
confidence: 91%
“…The axial stress transmitted across the knee joint increases substantially in the involved compartment after APM ( 25 ), which may worsen symptoms in patients with preexisting joint degeneration. The increased stress transmitted across the involved compartment can also lead to cartilage loss in patients without preexisting joint degeneration, which may have an adverse effect on clinical outcome over time ( 26 ).…”
Section: Musculoskeletal Imaging: Mr Outcome Prediction After Arthrosmentioning
confidence: 99%